1982
DOI: 10.1177/109719638200600102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging of Urea-Formaldehyde Foam On Thermal Conductance

Abstract: The thermal conductance of vertical panels was measured over a period of months. Urea formaldehyde foam filled the cavities of the panels. The conductance was found to increase with aging. The cause of the increase is due to shrinking and cracking of the foam. The variation of shrinkage and conductance with time are discussed and quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Kalthod and Knickle have reported that, approximately 20 months after installation, a urea formaldehyde foam had undergone an average linear shrinkage of 7.3 percent; their thermal data show that a panel containing 14-month-old foam transmitted heat 50 percent more readily than when newly formed [15]. Elsewhere, the same authors have observed that the extent to which fibrous insulation is fluffed can modify its heat-conduction property by 22 percent [16].…”
Section: E Insulation Performancementioning
confidence: 98%
“…Kalthod and Knickle have reported that, approximately 20 months after installation, a urea formaldehyde foam had undergone an average linear shrinkage of 7.3 percent; their thermal data show that a panel containing 14-month-old foam transmitted heat 50 percent more readily than when newly formed [15]. Elsewhere, the same authors have observed that the extent to which fibrous insulation is fluffed can modify its heat-conduction property by 22 percent [16].…”
Section: E Insulation Performancementioning
confidence: 98%